Scallop genome reveals molecular adaptations to semi-sessile life and neurotoxins - Li, Yuli; Sun, Xiaoqing; Hu, Xiaoli; Xun, Xiaogang; Zhang, Jinbo; Guo, Ximing; Jiao, Wenqian; Zhang, Lingling; Liu, Weizhi; Wang, Jing; Li, Ji; Sun, Yan; et al. (Nature communications, 2017)
Bivalve molluscs are descendants of an early-Cambrian lineage superbly adapted to benthic filter feeding. Adaptations in form and behavior are well recognized, but the underlying molecular mechanisms are largely unknown. Here, we investigate the genome, various transcriptomes, and proteomes of the scallop Chlamys farreri , a semi-sessile bivalve with well-developed adductor muscle, sophisticated eyes, and remarkable neurotoxin resistance. The scallop’s large striated muscle is energy-dynamic but not fully differentiated from smooth muscle. Its eyes are supported by highly diverse, intronless opsins expanded by retroposition for broadened spectral sensitivity. Rapid byssal secretion is enabled by a specialized foot and multiple proteins including expanded tyrosinases. The scallop uses hepatopancreas to accumulate neurotoxins and kidney to transform to high-toxicity forms through expanded sulfotransferases, probably as deterrence against predation, while it achieves neurotoxin resistance through point mutations in sodium channels. These findings suggest that expansion and mutation of those genes may have profound effects on scallop’s phenotype and adaptation. Bivalve molluscs have evolved various characteristics to adapt to benthic filter-feeding. Here, Li et al investigate the genome, transcriptomes and proteomes of scallop Chlamys farreri , revealing evidences of molecular adaptations to semi-sessile life and neurotoxins.